FACTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN DINI DI PROPINSI BANTEN - Riri, Rohanah; Juwita, Dessi; Nugraha, Rd. Deden Gumilar (JURNAL EDUCATION AND DEVELOPMENT, 2025)
WHO limits the age of adolescents from the age of 10 to 19 years, according to the Law of the Republic of Indonesia No. 16 of 2019, the age limit for marriage is that men and women are at least 19 years old. The impact caused by marriage at a young age is that the child's growth and development will be hampered. Teenage marriage has a negative impact on children's growth and development, not fulfilling the right to protection from violence and discrimination, children's civil rights, health rights, education rights, and children's social rights. (BPS, 2019). Based on 2019 SKAP data, Banten Province is in position 23, which is 27.1% (BKKBN, 2019). The inclusion criteria in the sample of this study are women of childbearing age who are married, living with a partner, divorced but the partner is still alive, divorced but the partner has died, the number of respondents is 1710 people. The data collection technique uses secondary data from the 2019 KKBPK Performance Survey and SKAP by looking at the Raw Women's Questionnaire (FQ) data with questions according to the variables studied. The results showed that there was an influence, namely Population Knowledge, Family Planning and KRR with a significance value/probability value (P) of 0.0005, Population information sources with a significance value/probability value of 0.000, family planning information sources with a significance/probability value of 0.027 and a source of KRR information with a significance value 0.000 The dominant variable that affects early marriage is the source of population information (OR = 1.775 95% CI 1.201-2.621). There needs to be information about the impact and risks of early marriage in schools so that people know the negative impact of early marriage.